If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15=-3(m+5)
We simplify the equation to the form, which is simple to understand
15=-3(m+5)
Reorder the terms in parentheses
15=+(-3m-15)
Remove unnecessary parentheses
+15=-3m-15
We move all terms containing m to the left and all other terms to the right.
+3m=-15-15
We simplify left and right side of the equation.
+3m=-30
We divide both sides of the equation by 03 to get m.
m=-10
| x^4+3x^3-3x^2-11x-6=0 | | 3x+4x-9=19 | | 3x+5=0.2(15x+10) | | p=s+6 | | 0.25+0.10(x+85)=15.25 | | y=15x-30 | | 0.25x+0.5(x+6)=3.90 | | 2(p-4)=10 | | 3x-5(x-4)=-6+3x+1 | | -20=4x+8 | | 81-6= | | -54x^3+24x=0 | | 15=7x+6-4x | | 0.25+0.10(x+15)=3.95 | | 9x+27-27=72-72 | | 63*56= | | 3+5+p= | | 60-6x=12x+15 | | 0.5x-1.36=12.34 | | 15=7x | | 26=8+u | | -3f=18-f | | -6x^2-x-4=0 | | 53-7x=15+12x | | 0=x^2+2y^2+4y-2x+1 | | d-23d= | | 28=5x+3(2x+11) | | (2xh)+(2xh)+(h+h)=180 | | 16x+9=15x-4 | | (X+7)(3x+5)=0 | | 3(4x-3.2)=5x-9.6 | | 3(2-3x)=52 |